Development of Snakes and Ladders Media on Solid Geometry Materials for Fifth Grade Students' Learning Interests - Fini May Putriani; Erfan Ramadhani; Arief Kuswidyanarko (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Mathematics is one of the subjects that students are less interested in, especially in elementary schools. The problems in elementary school are students do not focus on learning, are afraid to answer teacher questions, and make the class less active during the learning process. It is due to the lack of learning media compared to thematic learning during the mathematics learning process. Hence, this study aimed to develop a valid and practical snake and ladder learning media on solid geometry material and determine the effect on students' learning interest after using the media. The research method employed was the RD method with the 4-D developmental model. The subjects were 39 elementary school students in Palembang, South Sumatera. Through validation, educator, and student response questionnaires, data were collected. The results uncovered that the validators’ validation obtained a mean validation score of 88.13%, with a very valid category. The results of student responses based on trials got a mean score of 91.05%, with a very practical category. Besides, the student learning interest questionnaire results attained a mean score of 80.25%, with a very high category. It was not only seen in the results of filling out the student's interest in learning instruments but also during the learning process. Consequently, the learning process became active; students became interested in playing while learning and dared to answer questions voluntarily. It implies that this research is vital so that the learning media continues to develop to generate student learning interest, particularly in solid geometry mathematics subjects.